Congenital idiopathic knee dislocation: a clinical case useful for defining an etiological hypothesis, times and methods of treatment - Bacchini, Pier Luigi; Corsini, Tiziana; Manfredi, Piera; Concari, Galeazzo (Acta Biomedica Atenei Parmensis, 2025)
Congenital knee dislocation (genu recurvatum) is a rare condition, occurring in about 1 in 100,000 live births. It can be associated with genetic syndromes or neurological disorders, but also occurs as an isolated condition. Factors such as oligohydramnios, breech presentation, and other limb abnormalities are often related. This case report details the presentation of a newborn female delivered at 37 weeks by emergency cesarean section, who exhibited congenital left knee dislocation without any other abnormalities. Upon birth, the left leg was observed to be hyperextended, with the foot positioned toward the body and slight cyanosis on the plantar skin. Initial treatment involved non-pharmacological pain management, followed by a successful manual reduction of the dislocation and application of a splint. The joint remained stable after 60 days of treatment, with no recurrence noted. Genetic testing and other screenings returned normal results. The discussion suggests an idiopathic nature of the dislocation, as the absence of a prenatal diagnosis points to a potential late-acquired condition in pregnancy. Hypotheses include limited uterine space and fetal movements that could have contributed to hyperextension. Pressure exerted on the small fetal patella likely facilitated lateral displacement, allowing the dislocation to occur. Early intervention proved crucial to prevent long-term complications, though the rarity of this condition makes future prognosis difficult to predict.